Silver-based solid lubricating material as well as preparation method and application thereof

By using silver-based solid lubricating material, the problem of insufficient friction and wear performance of the brush wire and the friction pair of the sliding ring in a vacuum environment is solved, and the long service life of the conductive slip ring in a vacuum is achieved.

CN119752505AActive Publication Date: 2025-04-04LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411687214.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-04-04
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The friction and wear performance of the conductive slip ring between the brush wire and the friction pair of the slip ring in a vacuum environment is insufficient, resulting in a short service life.

Method used

A silver-based solid lubricating material is used, which consists of silver metal, tantalum metal, titanium metal, molybdenum disulfide, tungsten disulfide, niobium diselenide, graphite, antimony thioantionate, lanthanum fluoride and antimony trioxide, and is prepared by ball mill mixing and hot pressing sintering, and is applied in conductive slip rings to improve friction performance.

Benefits of technology

In a vacuum environment, the friction coefficient of the conductive slip ring is significantly improved and the service life is extended, the wear rate is reduced, and a long-life conductive slip ring is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752505A_ABST
    Figure CN119752505A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of conductive slip ring lubrication, in particular to a silver-based solid lubricating material and a preparation method and application thereof. The invention provides a silver-based solid lubricating material, which is prepared from the following raw materials in percentage by mass: 74 to 92 percent of metal silver, 0.5 to 1.5 percent of metal tantalum, 0.5 to 1.5 percent of metal titanium, 1.0 to 4.5 percent of molybdenum disulfide, 1.0 to 4.5 percent of tungsten disulfide, 1.0 to 4.5 percent of niobium diselenide, 0.5 to 1.5 percent of graphite, 1.5 to 3.5 percent of antimony thioantimonate, 0.5 to 1.0 percent of lanthanum fluoride and 1.5 to 3.5 percent of antimony trioxide. According to the silver-based solid lubricating material, the tribological performance of brush wires and a slip ring friction pair of the conductive slip ring in a vacuum environment can be improved, and then the service life of the conductive slip ring in the vacuum environment is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive slip ring lubrication, and in particular to a silver-based solid lubricating material and a preparation method and application thereof. Background Art

[0002] Conductive slip ring is a precision device that can realize signal and power transmission between rotating parts and stationary parts. In the field of aerospace, conductive slip rings are widely used in various occasions that require rotary communication, such as satellites, rockets or spacecraft. With the continuous advancement of aerospace technology and the rapid development of deep space aerospace, the life requirements of conductive slip rings are getting higher and higher. The friction and wear performance between the brush wire and the slip ring determines the life of the slip ring. Therefore, improving the friction and wear performance between the slip ring and the brush wire is one of the technical ways to achieve a long life (greater than 20 million revolutions) of the conductive slip ring. Summary of the invention

[0003] The purpose of the present invention is to provide a silver-based solid lubricant and a preparation method and application thereof. The silver-based solid lubricant can improve the tribological performance of the friction pair of the brush wire and the slip ring of the conductive slip ring in a vacuum environment, thereby increasing the service life of the conductive slip ring in a vacuum environment.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The invention provides a silver-based solid lubricating material. The raw materials for preparing the silver-based solid lubricating material include, by weight percentage, 74-92% of metallic silver, 0.5-1.5% of metallic tantalum, 0.5-1.5% of metallic titanium, 1.0-4.5% of molybdenum disulfide, 1.0-4.5% of tungsten disulfide, 1.0-4.5% of niobium diselenide, 0.5-1.5% of graphite, 1.5-3.5% of antimony thioantimonate, 0.5-1.0% of lanthanum fluoride and 1.5-3.5% of antimony trioxide.

[0006] Preferably, the raw materials for preparing the silver-based solid lubricating material include, by mass percentage: 78-88% metallic silver, 1.0-1.5% metallic tantalum, 1.0-1.5% metallic titanium, 2.0-4.5% molybdenum disulfide, 1.0-3.5% tungsten disulfide, 1.0-2.5% niobium diselenide, 0.5-1.0% graphite, 2.0-3.0% antimony thioantimonate, 0.8-1.0% lanthanum fluoride and 2.0-3.0% antimony trioxide;

[0007] The sum of the mass percentages of the raw materials for preparing the silver-based solid lubricating material is 100%.

[0008] The present invention also provides a method for preparing the silver-based solid lubricating material described in the above technical solution, comprising the following steps:

[0009] Molybdenum disulfide, tungsten disulfide, niobium diselenide, graphite, antimony thioantimonate, lanthanum fluoride and antimony trioxide are ball-milled to obtain a premixed non-metallic mixed powder;

[0010] The premixed non-metallic mixed powder, metallic silver, metallic tantalum and metallic titanium are mixed and then hot pressed and sintered to obtain the silver-based solid lubricating material.

[0011] Preferably, the particle sizes of the molybdenum disulfide, tungsten disulfide and niobium diselenide are independently 1 to 10 mm.

[0012] Preferably, the particle size of the graphite is 5 to 25 mm.

[0013] Preferably, the particle sizes of the antimony thioantimonate, lanthanum fluoride and antimony trioxide are independently ≤10 mm.

[0014] Preferably, the metallic silver is -200 mesh full powder; the particle sizes of the metallic tantalum and metallic titanium are independently <10 mm.

[0015] Preferably, the ball milling mixing time is 4 to 8 hours, and the mixing time is 2 to 6 hours.

[0016] Preferably, the sintering pressure of the hot pressing sintering is 30-80 MPa, the sintering temperature is 650-690° C., and the holding time is 2-6 h.

[0017] The present invention also provides the use of the silver-based solid lubricating material described in the above technical solution or the silver-based solid lubricating material prepared by the preparation method described in the above technical solution in a conductive slip ring.

[0018] The invention provides a silver-based solid lubricating material. The raw materials for preparing the silver-based solid lubricating material include, by weight percentage, 74-92% of metallic silver, 0.5-1.5% of metallic tantalum, 0.5-1.5% of metallic titanium, 1.0-4.5% of molybdenum disulfide, 1.0-4.5% of tungsten disulfide, 1.0-4.5% of niobium diselenide, 0.5-1.5% of graphite, 1.5-3.5% of antimony thioantimonate, 0.5-1.0% of lanthanum fluoride and 1.5-3.5% of antimony trioxide. The silver-based solid lubricant of the present invention is based on silver, and solid lubricants (molybdenum disulfide, tungsten disulfide, niobium diselenide and graphite) and film-forming additives (antimony thioantimonate, lanthanum fluoride and antimony trioxide) are added to have excellent transferability, film-forming performance and conductive lubrication performance; the silver-based solid lubricant is applied to the conductive slip ring and contacts the slip ring. Through the lubrication of the silver-based solid lubricant, the tribological performance of the friction pair of the brush wire and the slip ring of the conductive slip ring in a vacuum environment is improved, thereby achieving a long service life of the conductive slip ring in a vacuum. The results of the embodiment show that the friction coefficient of the silver-based solid lubricant of the present invention in a vacuum is 0.05-0.15, and the wear rate in a vacuum is 1.5×10 -5 ~8.0×10 -5 mm 3 / Nm. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a microstructure diagram of the silver-based solid lubricating material described in Example 1;

[0020] Figure 2 It is a schematic diagram of the structure of the conductive slip ring described in the application example, wherein 11 is a slip ring, 12 is a filamentary brush, 13 is a bracket, and 14 is a solid lubricating block. DETAILED DESCRIPTION

[0021] The invention provides a silver-based solid lubricating material. The raw materials for preparing the silver-based solid lubricating material include, by weight percentage, 74-92% of metallic silver, 0.5-1.5% of metallic tantalum, 0.5-1.5% of metallic titanium, 1.0-4.5% of molybdenum disulfide, 1.0-4.5% of tungsten disulfide, 1.0-4.5% of niobium diselenide, 0.5-1.5% of graphite, 1.5-3.5% of antimony thioantimonate, 0.5-1.0% of lanthanum fluoride and 1.5-3.5% of antimony trioxide.

[0022] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0023] In terms of mass percentage, the raw materials for preparing the silver-based solid lubricant of the present invention include 74-92% metallic silver, preferably 78-88%. In an embodiment of the present invention, the mass percentage of the metallic silver may be 83.5% or 86.7%. In the present invention, the metallic silver is used as a matrix material in the silver-based solid lubricant.

[0024] In terms of mass percentage, the raw material for preparing the silver-based solid lubricating material of the present invention includes 0.5-1.5% of tantalum metal, preferably 1.0-1.5%. In an embodiment of the present invention, the mass percentage of the tantalum metal can be 1.0% or 1.5%.

[0025] In the present invention, the metal tantalum as a hard phase can be dispersed in the silver-based solid lubricant and become a microscopic support point of the friction surface of the silver-based solid lubricant, thereby improving the hardness and wear resistance of the silver-based solid lubricant.

[0026] In terms of mass percentage, the raw material for preparing the silver-based solid lubricant of the present invention includes 0.5-1.5% of titanium metal, preferably 1.0-1.5%. In the embodiment of the present invention, the mass percentage of the titanium metal can be 1.0% or 1.5%.

[0027] In the present invention, since there is a small amount of atomic oxygen in space, metallic titanium can react with atomic oxygen first, thereby preventing oxidation of molybdenum disulfide. Meanwhile, the presence of titanium can enhance the strength of the transfer film of the silver-based solid lubricant.

[0028] In terms of mass percentage, the raw materials for preparing the silver-based solid lubricating material of the present invention include 1.0-4.5% molybdenum disulfide, preferably 2.0-4.5%. In an embodiment of the present invention, the mass percentage of the molybdenum disulfide can be 3.5% or 2.0%.

[0029] In terms of mass percentage, the raw materials for preparing the silver-based solid lubricating material of the present invention include 1.0-4.5% tungsten disulfide, preferably 1.0-3.5%. In an embodiment of the present invention, the mass percentage of tungsten disulfide can be 3.0% or 1.5%.

[0030] According to the mass percentage, the raw material for preparing the silver-based solid lubricant of the present invention includes 1.0-4.5% niobium diselenide, preferably 1.0-2.5%. In the embodiment of the present invention, the mass percentage of the niobium diselenide can be 2.0% or 1.0%.

[0031] According to the percentage by mass, the raw material for preparing the silver-based solid lubricant of the present invention includes 0.5-1.5% graphite, preferably 0.5-1.0%. In the embodiment of the present invention, the percentage by mass of the graphite can be 1.0%.

[0032] In the present invention, the molybdenum disulfide, tungsten disulfide, niobium diselenide and graphite have a synergistic effect in a vacuum environment after being compounded. The present invention regulates the friction transfer performance of the silver-based solid lubricant material, the friction reduction performance and anti-wear performance of the solid lubricant transfer film, and the conductive performance by adjusting the content ratio of the above four substances.

[0033] According to the mass percentage, the raw materials for preparing the silver-based solid lubricating material of the present invention include 1.5-3.5% antimony thioantimonate, preferably 2.0-3.0%. In the embodiment of the present invention, the mass percentage of the antimony thioantimonate can be 2.0%.

[0034] In the present invention, the antimony thioantimonate can improve the integrity of the transfer film.

[0035] According to the mass percentage, the raw material for preparing the silver-based solid lubricant of the present invention includes 0.5-1.0% lanthanum fluoride, preferably 0.8-1.0%. In the embodiment of the present invention, the mass percentage of the lanthanum fluoride can be 1.0% or 0.8%.

[0036] In the present invention, the lanthanum fluoride can improve the wear resistance of the transfer film.

[0037] According to the mass percentage, the raw material for preparing the silver-based solid lubricant of the present invention includes 1.5-3.5% antimony dioxide, preferably 2.0-3.0%. In the embodiment of the present invention, the mass percentage of the antimony trioxide can be 2.0%.

[0038] In the present invention, the antimony dioxide can reduce the harmfulness of the transfer film being oxidized to generate molybdenum trioxide.

[0039] In the present invention, the composite use of antimony thioantimonate, lanthanum fluoride and antimony trioxide can improve the integrity and anti-wear performance of the silver-based solid lubricant transfer film of the present invention and reduce the harmfulness of oxidation of the molybdenum disulfide transfer film to generate molybdenum trioxide.

[0040] The present invention also provides a method for preparing the silver-based solid lubricating material described in the above technical solution, comprising the following steps:

[0041] Molybdenum disulfide, tungsten disulfide, niobium diselenide, graphite, antimony thioantimonate, lanthanum fluoride and antimony trioxide are ball-milled to obtain a premixed non-metallic mixed powder;

[0042] The premixed non-metallic mixed powder, metallic silver, metallic tantalum and metallic titanium are mixed and then hot pressed and sintered to obtain the silver-based solid lubricating material.

[0043] The invention ball-mills and mixes molybdenum disulfide, tungsten disulfide, niobium diselenide, graphite, antimony thioantimonate, lanthanum fluoride and antimony trioxide to obtain premixed non-metallic mixed powder.

[0044] In the present invention, the particle sizes of molybdenum disulfide, tungsten disulfide and niobium diselenide are preferably 1 to 10 mm, the particle size of graphite is preferably 5 to 25 mm, and the particle sizes of antimony thioantimonate, lanthanum fluoride and antimony trioxide are preferably ≤ 10 mm.

[0045] In the present invention, the ball milling speed is preferably 100-200 rpm, more preferably 120-180 rpm, and the time is preferably 4-8 hours, more preferably 5-6 hours. In an embodiment of the present invention, the ball milling speed can be 150 rpm, and the time can be 6 hours or 5 hours.

[0046] After obtaining the premixed non-metallic mixed powder, the present invention mixes the premixed non-metallic mixed powder, metal silver, metal tantalum and metal titanium, and then performs hot pressing and sintering to obtain the silver-based solid lubricating material.

[0047] In the present invention, the metallic silver is preferably -200 mesh full powder; the particle sizes of the metallic tantalum and metallic titanium are independently preferably <10 mm.

[0048] In the present invention, the mixing method is preferably ballless mixing; the rotation speed of the ballless mixing is preferably 100 to 200 rpm, more preferably 120 to 180 rpm; the time is preferably 2 to 6 hours, more preferably 4 to 5 hours. In an embodiment of the present invention, the rotation speed of the ballless mixing can be 150 rpm, and the time can be 4 hours. In the present invention, the ballless mixing is preferably carried out in a ball mill.

[0049] In the present invention, the sintering pressure of the hot pressing sintering is preferably 30-80MPa, more preferably 40-60MPa; the sintering temperature is preferably 650-690°C, more preferably 660-680°C; the holding time is preferably 2-6h, more preferably 3-5h. In an embodiment of the present invention, the sintering pressure of the hot pressing sintering can be 50MPa, the sintering temperature can be 670°C or 680°C, and the holding time can be 3h. In an embodiment of the present invention, the hot pressing sintering is specifically to place the material obtained after the ball-free mixing in a steel mold for hot pressing sintering.

[0050] The present invention also provides the use of the silver-based solid lubricating material described in the above technical solution or the silver-based solid lubricating material prepared by the preparation method described in the above technical solution in a conductive slip ring.

[0051] In the present invention, the application method is preferably to prepare the silver-based solid lubricating material described in the above technical solution into a solid lubricating block, and then install it into the conductive slip ring. The present invention does not have any special restrictions on the preparation process of the solid lubricating block, and can be carried out using a process well known to those skilled in the art. In the embodiment of the present invention, the structure of the conductive slip ring (such as Figure 2 The invention discloses a slip ring 11 comprising a filamentary brush 12, a bracket 13 and a solid lubricating block 14; the filamentary brush 12 and the solid lubricating block 14 are respectively mounted on opposite sides of the bracket, and the filamentary brush 12 and the solid lubricating block 14 are respectively in contact with the slip ring 11. In the present invention, the contact pressure is preferably 10 to 50 kPa, more preferably 20 to 30 kPa. In the present invention, the solid lubricating block 14 is a solid lubricating block prepared from the silver-based solid lubricating material described in the above technical solution, and the curvature of the friction surface of the solid lubricating block 14 is consistent with the curvature of the slip ring 11.

[0052] In the present invention, during the rotation of the slip ring, the solid lubricant in the solid lubricant block is transferred to the surface of the slip ring to form an extremely thin solid lubricant film by friction between the solid lubricant block and the surface of the slip ring under a certain pressure, thereby achieving lubrication of the brush wire / slip ring friction pair. The extremely thin lubricant film formed on the surface of the slip ring has a certain conductivity, and the generated resistance is controlled within the acceptable range of the slip ring circuit. The lubricant block continuously provides lubricant to the friction surface of the slip ring, thereby greatly extending the life of the conductive slip ring.

[0053] The silver-based solid lubricating material provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0054] Example 1

[0055] Preparation raw materials and their mass percentage content: metal silver (Ag, 83.5%) powder particle size is -200 mesh, purity is 99.9%; metal tantalum (Ta, 1.0%) and metal titanium (Ti, 1.0%) particle sizes are 1-10mm, purity is 99.9%; molybdenum disulfide (MoS2, 3.5%), tungsten disulfide (WS2, 3.0%) and niobium diselenide (NbSe2, 2.0%) particle sizes are 1-10mm, purity is 99.5%; graphite (C, 1.0%) particle size is 5-25mm, purity is 99.0%; antimony thioantimonate (SbSbS2, 2.0%), lanthanum fluoride (LaF3, 1.0%) and antimony trioxide (Sb2O3, 2.0%) particle sizes are 1-10mm, purity is 99.5%.

[0056] Preparation method: molybdenum disulfide, tungsten disulfide, niobium diselenide, graphite, antimony thioantimonate, lanthanum fluoride and antimony trioxide are ball-milled and mixed in a ball mill (rotation speed is 150 rpm, time is 6 hours) to obtain a premixed non-metallic mixed powder;

[0057] The premixed non-metallic mixed powder, metallic silver, metallic tantalum and metallic titanium are mixed without balls in a ball mill (rotation speed is 150 rpm, time is 4 hours), the obtained mixed powder is hot pressed and sintered (temperature is 680° C., holding time is 3 hours, sintering pressure is 50 MPa), and cooled in the furnace to obtain a silver-based solid lubricating material;

[0058] Figure 1 is a microstructure diagram of the silver-based solid lubricant, wherein the white part is a metal component and the black part is a non-metal component, forming a solid lubricant with metal as a matrix and non-metal as a lubricant;

[0059] The performance test standards and results of the silver-based solid lubricant are shown in Table 1:

[0060] Table 1 Performance test standards and results of the silver-based solid lubricant materials

[0061] Test items Test Standards Test Results Brinell hardness / HB GB / T231.1-2018 32 Yield strength / MPa GB / T7314-2017 129 Friction coefficient GB / T12444-2006 0.09 <![CDATA[Wear rate / ×10 -5 mm 3 / (Nm)]]> GB / T12444-2006 3.6

[0062] Example 2

[0063] Preparation raw materials and their mass percentage content: metal silver (Ag, 86.7%) powder particle size is -200 mesh, purity is 99.9%; metal tantalum (Ta, 1.5%) and metal titanium (Ti, 1.5%) particle sizes are 1-10mm, purity is 99.9%; molybdenum disulfide (MoS2, 2.0%), tungsten disulfide (WS2, 1.5%) and niobium diselenide (NbSe2, 1.0%) particle sizes are 1-10mm, purity is 99.5%; graphite (C, 1.0%) particle size is 5-25mm, purity is 99.0%; antimony thioantimonate (SbSbS2, 2.0%), lanthanum fluoride (LaF3, 0.8%) and antimony trioxide (Sb2O3, 2.0%) particle sizes are 1-10mm, purity is 99.5%.

[0064] Preparation method: molybdenum disulfide, tungsten disulfide, niobium diselenide, graphite, antimony thioantimonate, lanthanum fluoride and antimony trioxide are ball-milled and mixed in a ball mill (speed of 150 rpm, time of 5 hours) to obtain a premixed non-metallic mixed powder;

[0065] The premixed non-metallic mixed powder, metallic silver, metallic tantalum and metallic titanium are mixed without balls in a ball mill (rotation speed is 150 rpm, time is 4 hours), the obtained mixed powder is hot pressed and sintered (temperature is 670° C., holding time is 3 hours, sintering pressure is 50 MPa), and cooled in the furnace to obtain a silver-based solid lubricating material;

[0066] The performance test standards and results of the silver-based solid lubricant are shown in Table 2:

[0067] Table 2 Performance test standards and results of the silver-based solid lubricant materials

[0068] Test items Test Standards Test Results Brinell hardness / HB GB / T231.1-2018 63 Yield strength / MPa GB / T7314-2017 196 Friction coefficient GB / T12444-2006 0.13 <![CDATA[Wear rate / ×10 -5 mm 3 / (Nm)]]> GB / T12444-2006 1.9

[0069] Application Examples

[0070] The silver-based solid lubricating material described in Example 1 is processed into a solid lubricating block and installed in a Figure 2 In the conductive slip ring shown in FIG. Figure 2 The invention discloses a slip ring 11 comprising a filamentary brush 12, a bracket 13 and a solid lubricating block 14; the filamentary brush 12 and the solid lubricating block are respectively installed on opposite sides of the bracket, and the bracket 13 and the solid lubricating block 14 are in contact with the slip ring 11, and there is a pressure of 20 kPa; the solid lubricating block 14 is rubbed with the slip ring 11 to transfer the solid lubricant to the surface of the slip ring 11 to form a conductive solid lubricating film, thereby providing effective lubrication for the friction pair between the brush 12 and the slip ring 11, and the curvature of the friction surface of the solid lubricating block 14 is consistent with the curvature of the slip ring; the life of the conductive slip ring is verified to be 58 million revolutions on a ground bench test machine (in a vacuum environment).

[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A silver-based solid lubricating material, characterized in that: Calculated by mass percentage, the raw materials for preparing the silver-based solid lubricating material include: 74-92% metallic silver, 0.5-1.5% metallic tantalum, 0.5-1.5% metallic titanium, 1.0-4.5% molybdenum disulfide, 1.0-4.5% tungsten disulfide, 1.0-4.5% niobium diselenide, 0.5-1.5% graphite, 1.5-3.5% antimony thioantimonate, 0.5-1.0% lanthanum fluoride and 1.5-3.5% antimony trioxide.

2. The silver-based solid lubricating material according to claim 1, characterized in that: The raw materials for preparing the silver-based solid lubricating material include, by mass percentage, 78-88% of metallic silver, 1.0-1.5% of metallic tantalum, 1.0-1.5% of metallic titanium, 2.0-4.5% of molybdenum disulfide, 1.0-3.5% of tungsten disulfide, 1.0-2.5% of niobium diselenide, 0.5-1.0% of graphite, 2.0-3.0% of antimony thioantimonate, 0.8-1.0% of lanthanum fluoride and 2.0-3.0% of antimony trioxide; The sum of the mass percentages of the raw materials for preparing the silver-based solid lubricating material is 100%.

3. The method for preparing the silver-based solid lubricating material according to claim 1 or 2, characterized in that: The following steps are involved: Molybdenum disulfide, tungsten disulfide, niobium diselenide, graphite, antimony thioantimonate, lanthanum fluoride and antimony trioxide are ball-milled to obtain a premixed non-metallic mixed powder; The premixed non-metallic mixed powder, metallic silver, metallic tantalum and metallic titanium are mixed without balls and then hot pressed and sintered to obtain the silver-based solid lubricating material.

4. The preparation method according to claim 3, characterized in that: The particle sizes of the molybdenum disulfide, tungsten disulfide and niobium diselenide are independently 1 to 10 mm.

5. The preparation method according to claim 3, characterized in that: The particle size of the graphite is 5 to 25 mm.

6. The preparation method according to claim 3, characterized in that: The particle sizes of the antimony thioantimonate, lanthanum fluoride and antimony trioxide are independently ≤10 mm.

7. The preparation method according to claim 3, characterized in that: The metallic silver is -200 mesh full powder; the particle sizes of the metallic tantalum and metallic titanium are independently <10 mm.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The ball milling mixing time is 4 to 8 hours, and the mixing time is 2 to 6 hours.

9. The preparation method according to claim 3, characterized in that: The sintering pressure of the hot pressing sintering is 30-80 MPa, the sintering temperature is 650-690° C., and the heat preservation time is 2-6 hours.

10. Use of the silver-based solid lubricant according to claim 1 or 2 or the silver-based solid lubricant prepared by the preparation method according to any one of claims 3 to 9 in lubrication of conductive slip rings.

Citation Information

Patent Citations

  • Electric brush-sliding ring system made of silver-tungsten disulfide composite materials

    CN103447531A

  • Lubricating composition based on metal nanoparticles

    CN106103670A

  • Embedded high-temperature composite solid lubricating material for self-lubricating bearing and preparation method thereof

    CN107189840A

  • Nano-composite lubricating ultralow-abrasion aerospace electric contact material and preparation method thereof

    CN107312949A

  • Space solid lubricant coating and preparation method thereof

    CN109401812A